2022
DOI: 10.3390/agriculture12101712
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Different ω-6 to ω-3 Fatty Acid Ratios Affects the Sustainability of Performance, Egg Quality, Fatty Acid Profile, Immunity and Egg Health Indices of Laying Hens

Abstract: The supplementation of different ω-6/ω-3 ratio to the diets of the laying hens has been studied to evaluate the effects on performance, egg quality, egg health indices, egg fatty acid profiles, and immune response. One-hundred and twenty, 50-weeks-old hens were divided into three groups fed diets with different ω-6/ω-3 polyunsaturated fatty acids (PUFA) at ratio: 16.7:1, 9.3:1, and 5.5:1, respectively. Each group contained eight replicates of five hens. Hens fed the diet with the highest ω-6/ω-3 ratio had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…However, although birds fed algal oil diets had similar eggshell quality values to those fed the standard diet, some surprising differences existed between birds fed algal oils. Previous research reported conflicting effects of feeding n-3 FA-enriched diets on eggshell quality; for example, reduction ( Attia et al, 2022 ) and no effects ( Neijat et al, 2016 ). As expected, feed intake, HDEP, FCR, egg weight and egg mass increased with hen age ( Hanlon et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, although birds fed algal oil diets had similar eggshell quality values to those fed the standard diet, some surprising differences existed between birds fed algal oils. Previous research reported conflicting effects of feeding n-3 FA-enriched diets on eggshell quality; for example, reduction ( Attia et al, 2022 ) and no effects ( Neijat et al, 2016 ). As expected, feed intake, HDEP, FCR, egg weight and egg mass increased with hen age ( Hanlon et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%